PERLINDUNGAN HUKUM TERHADAP PENANGKAPAN NELAYAN TRADISIONAL INDONESIA DARI NUSA TENGGARA TIMUR DI PULAU PASIR BERDASRKAN PERSPEKTIF HUKUM INTERNASIONAL - Ketut Awet Putra Karyawan; Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Jurnal Ilmu Hukum Sui Generis, 2023)
This study aims to understand and analyze the mechanisms and regulations of international law that apply in providing protection and settlement as well as legal constraints faced against the case of catching traditional Indonesian fishermen, East Nusa Tenggara in Pualu Pasir which is Australian sovereignty. The research method used is normative legal research using 3 approaches, namely the approach to legislation, history, and cases that are processed with descriptive techniques that produce legal arguments. The results showed that legal protection against the fishing of traditional fishermen is regulated in three bilateral agreements between the governments of Indonesia and Australia: MoU BOX 1974, MoU BOX 1981, and Agreed Minute 1989. The purpose of this agreement is to ensure the rights of Indonesia's traditional fisheries. In the realm of international law, Article 51 paragraph (1982) of the Convention on the Law of the Sea (UNCLOS 1982) also clearly outlines the rights of traditional fishermen related to fisheries, but there is still a need for amendments to the bilateral agreement, as well as the main obstacles related to views on traditional fishers including differences in territorial boundaries, fishing gear used, and the economic sustainability of fishermen. The solution involves strengthening national regulations, legal recognition of traditional fishermen's rights, boundary agreements, and protection of marine resources in the area. However, differences in views, efforts to maintain traditions, pressure on resources, and economic challenges remain obstacles in addressing abuses committed by traditional fishermen in the Sand Island region.